A multi-institutional survey on the practice of endoscopic ultrasound (EUS) guided pseudocyst drainage in the Asian EUS group - Teoh, Anthony Yuen Bun; Ho, Lawrence Khek Yu; Dhir, Vinay Kumar; Jin, Zhen Dong; Kida, Mitsuhiro; Seo, Dong Wan; Wang, Hsui Po; Yang, Ai Ming; Binmoeller, Kenneth Frank; Varadarajulu, Shyam (Endoscopy International Open, 2015)
Background: There is a lack of consensus on how endoscopic ultrasound (EUS) guided pseudocyst drainage should be performed. This survey was carried out amongst members of the Asian Endoscopic Ultrasonography Group (AEG) to describe their practices in performing this procedure.Methods: This was an Asia wide multi-institutional survey amongst members of the Asian EUS group conducted between November and December 2013. The responses to a 19-question survey with regard to the practice of pseudocyst drainage were obtained.Results: In total, 19 endoscopists responded to the questionnaire and the mean (SD) number of procedures performed by each endoscopist was 87.95 (40); 42.2 % believed that prior endoscopic retrograde cholangiopancreatography (ERCP) is required and pancreatic duct stenting is indicated in patients with pancreatic duct disruption; 47.4 % used tapered catheters for track dilation and 42.1 % used the cystotome; 84.1 % would dilate the track up to 8 to 10 mm in size. Metallic stents were used by 10.5 % of the respondents and transcystic catheters were employed by 26.3 %. Those who were more experienced in the procedure tended to use the cystotome more frequently (P = 0.02) and removed the stents in less than 3 months after insertion (P = 0.011).Conclusion: This was the first Asia wide survey in the practice of pseudocyst drainage. There were wide variations in practice and randomized studies are urgently needed to establish the best approach for management of this condition. There is also a pressing need for establishment of a consensus for safe practices.